Ranks and positions, administrative classes in the Kokan Khanate - Iskandarov Sultonbek Mavlon og'li (Genius Journals, 2023)
This article contains brief information about the positions and titles of the Kokan Khanate, but the significance of the given positions and titles in the history of the Khanate is explained in detail.
Keywords: Mingboshi; Koshbegi; Voli